Federated States of Micronesia : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2004 Article IV Consultation on the Federated States of Micronesia (FSM) focuses on economic developments and policies. Fiscal and structural reforms are needed for the FSM to achieve self-sufficiency. The large government sector will be increasingly unsustainable given coming declines in grants. Fiscal adjustment will need to comprise both expenditure cuts and revenue measures. Structural reform priorities should include improvements to the legal framework for land use, foreign investment, and lending.